Pregnancy Rates after Intrauterine Insemination in Moderate to Severe Endometriosis: A Systematic Review and Meta-analysis of Observational Studies. Issue 3 (July 2017) - Van Der Houwen, Lisette E.E.; Schreurs, Anneke M.F.; Schats, Roel; Kaspers, Pam; Lambalk, Cornells B.; Hompes, Peter G.A.; Mijatovic, Velja
To evaluate the efficacy and safety of intrauterine insemination (IUI) in moderate to severe endometriosis patients, a systematic review and meta-analysis was conducted since the role of this treatment strategy in these patients is a matter of debate in the literature. Systematic searches were performed in PubMed, EMBASE, Cinahl, and The Cochrane Library from inception to September 1, 2016. Studies including moderate to severe endometriosis patients reporting pregnancy rates after IUI were selected. The primary outcome was live birth after IUI treatment compared to expectant management. Secondary noncomparative outcomes were live birth and clinical pregnancy, which were presented as weighed mean pregnancy rates. Nineteen articles (2 unclear design, 11 retrospective, 6 prospective) were included for the analysis. Our primary outcome measure was only addressed by one study, showing an odds ratio of 1.77 (95% confidence interval [CI], 0.86–3.63) on live birth favoring IUI versus no treatment. The calculated weighed mean live birth and clinical pregnancy rate per patient was 20.3% (95% CI, 11.2–29.4) and 32.7% (95% CI, 21.3– 44.0), respectively. This meta-analysis of observational data showed that IUI could be a feasible treatment in moderate to severe endometriosis. Whether this treatment should be structurally offered prior to in vitro fertilization needs to be investigated in a randomized, controlled trial, including time-to-pregnancy, safety, and cost-effectiveness.